The Effect of Product Standards on Agricultural Exports - Ferro, Esteban (Elsevier, 2014)
We introduce a standards restrictiveness index to analyze the impact that food safety standards have on international exports of agricultural products. Our new measure of standards restrictiveness is created using maximum residue levels of pesticides for 61 importing countries and 66 different products. The index accounts for both the number of pesticides regulated for each product and the allowable level for those pesticides by each importer. The findings suggest that more restrictive standards are associated, on average, with a lower probability of observing trade. However, after controlling for sample selection and the proportion of exporting firms in a gravity model, the analysis finds that the effect of standards on trade intensity in most cases is indistinguishable from zero. This is consistent with the assumption that meeting stringent standards increases primarily the fixed cost to export to a destination. Once a firm adjusts its production to comply with the standards of a foreign market, those standards do not impact the intensity of exports to that market. Finally, our results suggest that exports from developing countries are particularly constrained by stricter standards.